Superexploração da força de trabalho na contemporaneidade brasileira: trabalhadores da indústria da construção civil em Fortaleza - Rodrigues Júnior, Natan dos Santos (2019)
The objective of this paper is to analyze the changes in the profile and working conditions, as well as the new challenges for the workers' political union union in the construction industry, in Fortaleza, considering the deepening of the economic crisis in Brazil, in 2015, and the circuits of overexploitation of the workforce in the processes of the 2016 coup. To this end, it is based on the appropriation of bibliography of contemporary authors who make themselves classical, as references for study, and it is worth highlighting the formulations of thinkers of the Marxist Theory of Dependence - TMD in particular Ruy Mauro Marini, Jaime Osorio and Mathias Seibel Luce; the collection of macroeconomic data sets and the Brazilian labor market, using secondary sources available through the internet, especially from the Intersindical Department of Statistics and Socioeconomic Studies - DIEESE; and field research, with observation and interviews with workers working in the field of construction in Fortaleza. The precariousness of work in the country, which has occurred in recent decades and brutally intensified since the 2016 Coup, especially with the Labor Counter-Reform, brings up discussions about the overexploitation of the workforce as a founding element of dependence. Brazil and a driver of capital accumulation in Brazil at present. This formulation guides the central hypothesis of this research, about the existence of an intensification of the overexploitation of the workforce in the civil construction in Fortaleza.